Chinese (Taiwan) yearbook of international law and affairs. - Ma, Yingjiu (Chinese (Taiwan) Yearbook of International Law and Affairs, 2020)
Volume 36 of the Chinese (Taiwan) Yearbook of International Law and Affairs publishes scholarly articles and essays on international and transnational law, as well as compiles official documents on the state practice of the Republic of China (ROC) in 2018. The Yearbook publishes on multi-disciplinary topics with a focus on international and comparative law issues regarding Taiwan, Mainland China and the Asia-Pacific. Questions and comments can be directed to the editorial board of the Yearbook by email at yearbook@nccu.edu.tw.